Application of high temperature heat pipe in hypersonic vehicles thermal protection - Bai, Tong; Zhang, Hong; Xu, Hui (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2011)
In order to develop further the application of high temperature heat pipe in hypersonic vehicles thermal protection, the principles and characteristics of high temperature heat pipe used in hypersonic vehicles thermal protection were introduced. The methods of numerical simulation, theory analysis and experiment research were utilized to analyze the frozen start-up and steady state characteristic of the heat pipe as well as the machining improvement for fabricating irregularly shaped heat pipe which is suitable for leading edge of hypersonic vehicles. The results indicate that the frozen start-up time of heat pipe is long (10 min) and there exists large temperature difference along the heat pipe (47 °C/cm), but the heat pipe can reduce the temperature in stagnation area of hypersonic vehicles from 1 926 to 982 °C and work normally during 1 000–1 200°C. How to improve the maximum heat transfer capability and reduce the time needed for start-up from frozen state of the heat pipe by optimizing thermostructure such as designing of a novel wick with high performance is the key point in hypersonic vehicles thermal protection of heat pipe.